Developing Speaking Instruction Through Whole Brain Teaching for Tenth Grader at SMA Swasta Nur Azizi Tanjung Morawa in Academic Year 2023/2024 - Revi Restu Ayanda; Didik Santoso (PT Inovasi Pratama Internasional, 2023)
The objective of this developmental research is to develop a model of speaking instruction for tenth grader through whole brain teaching. The data of this study consisted of quantitative and qualitative data. The data sources were learners, teacher, and expert in speaking instruction design. Data were collected by using observation, questionnaires, and document. The speaking instruction were developed in four steps: (1) analyzing the existing speaking instruction, (2) carrying out needs analysis, (3) developing speaking instruction and (4) validating them. Data were analysed using percentages for quantitative data. Thematic Analysis is implemented to analyze the data. Thematic analysis that is one of method which used identifying, analyzing, and reporting patterns of themes in data and it minimally organizes and describes the data set in detail (Braun & Clarke, 2006). The result of this research was a theoretical model of speaking instruction based on whole brain teaching containing: the components of speaking and the procedure of whole brain teaching.